Techniques for preventing hypotension during spinal anaesthesia for caesarean section - Chooi, Cheryl (Cochrane Database Syst Rev, 2020)
BACKGROUND: Maternal hypotension is the most frequent complication of spinal anaesthesia for caesarean section. It can be associated with nausea or vomiting and may pose serious risks to the mother (unconsciousness, pulmonary aspiration) and baby (hypoxia, acidosis, neurological injury). OBJECTIVES: To assess the effects of prophylactic interventions for hypotension following spinal anaesthesia for caesarean section. SEARCH METHODS: We searched Cochrane Pregnancy and Childbirth's Trials Register (9 August 2016) and reference lists of retrieved studies. SELECTION CRITERIA: Randomised controlled trials, including full texts and abstracts, comparing interventions to prevent hypotension with placebo or alternative treatment in women having spinal anaesthesia for caesarean section. We excluded studies if hypotension was not an outcome measure. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed study quality and extracted data from eligible studies. We report 'Summary of findings' tables using GRADE. MAIN RESULTS: We included 125 studies involving 9469 women. Interventions were to prevent maternal hypotension following spinal anaesthesia only, and we excluded any interventions considered active treatment. All the included studies reported the review's primary outcome. Across 49 comparisons, we identified three intervention groups: intravenous fluids, pharmacological interventions, and physical interventions. Authors reported no serious adverse effects with any of the interventions investigated. Most trials reported hypotension requiring intervention and Apgar score of less than 8 at five minutes as the only outcomes. None of the trials included in the comparisons we describe reported admission to neonatal intensive care unit. Crystalloid versus control (no fluids) Fewer women experienced hypotension in the crystalloid group compared with no fluids (average risk ratio (RR) 0.84, 95% confidence interval (CI) 0.72 to 0.98; 370 women; 5 studies; low‐quality evidence). There was no clear difference between groups in numbers of women with nausea and vomiting (average RR 0.19, 95% CI 0.01 to 3.91; 1 study; 69 women; very low‐quality evidence). No baby had an Apgar score of less than 8 at five minutes in either group (60 babies, low‐quality evidence). Colloid versus crystalloid Fewer women experienced hypotension in the colloid group compared with the crystalloid group (average RR 0.69, 95% CI 0.58 to 0.81; 2009 women; 27 studies; verylow‐quality evidence). There were no clear differences between groups for maternal hypertension requiring intervention (average RR 0.64, 95% CI 0.09 to 4.46, 3 studies, 327 women; very low‐quality evidence), maternal bradycardia requiring intervention (average RR 0.98, 95% CI 0.54 to 1.78, 5 studies, 413 women; very low‐quality evidence), nausea and/or vomiting (average RR 0.89, 95% CI 0.66 to 1.19, 14 studies, 1058 women, I² = 29%; very low‐quality evidence), neonatal acidosis (average RR 0.83, 95% CI 0.15 to 4.52, 6 studies, 678 babies; very low‐quality evidence), or Apgar score of less than 8 at five minutes (average RR 0.24, 95% CI 0.03 to 2.05, 10 studies, 730 babies; very low‐quality evidence). Ephedrine versus phenylephrine There were no clear differences between ephedrine and phenylephrine groups for preventing maternal hypotension (average RR 0.92, 95% CI 0.71 to 1.18; 401 women; 8 studies; very low‐quality evidence) or hypertension (average RR 1.72, 95% CI 0.71 to 4.16, 2 studies, 118 women, low‐quality evidence). Rates of bradycardia were lower in the ephedrine group (average RR 0.37, 95% CI 0.21 to 0.64, 5 studies, 304 women, low‐quality evidence). There was no clear difference in the number of women with nausea and/or vomiting (average RR 0.76, 95% CI 0.39 to 1.49, 4 studies, 204 women, I² = 37%, very low‐quality evidence), or babies with neonatal acidosis (average RR 0.89, 95% CI 0.07 to 12.00, 3 studies, 175 babies, low‐quality evidence). No baby had an Apgar score of less than 8 at five minutes in either group (321 babies; low‐quality evidence). Ondansetron versus control Ondansetron administration was more effective than control (placebo saline) for preventing hypotension requiring treatment (average RR 0.67, 95% CI 0.54 to 0.83; 740 women, 8 studies, low‐quality evidence), bradycardia requiring treatment (average RR 0.49, 95% CI 0.28 to 0.87; 740 women, 8 studies, low‐quality evidence), and nausea and/or vomiting (average RR 0.35, 95% CI 0.24 to 0.51; 653 women, 7 studies, low‐quality evidence). There was no clear difference between the groups in rates of neonatal acidosis (average RR 0.48, 95% CI 0.05 to 5.09; 134 babies; 2 studies, low‐quality evidence) or Apgar scores of less than 8 at five minutes (284 babies, low‐quality evidence). Lower limb compression versus control Lower limb compression was more effective than control for preventing hypotension (average RR 0.61, 95% CI 0.47 to 0.78, 11 studies, 705 women, I² = 65%, very low‐quality evidence). There was no clear difference between the groups in rates of bradycardia (RR 0.63, 95% CI 0.11 to 3.56, 1 study, 74 women, very low‐quality evidence) or nausea and/or vomiting (average RR 0.42, 95% CI 0.14 to 1.27, 4 studies, 276 women, I² = 32%, very‐low quality evidence). No baby had an Apgar score of less than 8 at five minutes in either group (130 babies, very low‐quality evidence). Walking versus lying There was no clear difference between the groups for women with hypotension requiring treatment (RR 0.71, 95% CI 0.41 to 1.21, 1 study, 37 women, very low‐quality evidence). Many included studies reported little to no information that would allow an assessment of their risk of bias, limiting our ability to draw meaningful conclusions. GRADE assessments of the quality of evidence ranged from very low to low. We downgraded evidence for limitations in study design, imprecision, and indirectness; most studies assessed only women scheduled for elective caesarean sections. External validity also needs consideration. Readers should question the use of colloids in this context given the serious potential side effects such as allergy and renal failure associated with their administration. AUTHORS' CONCLUSIONS: While interventions such as crystalloids, colloids, ephedrine, phenylephrine, ondansetron, or lower leg compression can reduce the incidence of hypotension, none have been shown to eliminate the need to treat maternal hypotension in some women. We cannot draw any conclusions regarding rare adverse effects associated with use of the interventions (for example colloids) due to the relatively small numbers of women studied.